Factors influencing outcomes of endoprosthetic reconstruction of the distal end of the humerus. Issue 2 (March 2019) - Chebli, Caroline M.; Crimi, Alberto; Letson, Douglas; Binitie, Odion
Abstract : Background: Reconstruction of the distal humerus with modular endoprostheses is an uncommon procedure. We report the outcomes from a single institution of distal humeral reconstructions with a modular endoprosthesis. Methods: A retrospective chart review of our database from 1/1/2001-12/31/2016 identified 20 patients who received a distal humeral endoprosthesis. The time to failure, type of failure, and final range of motion were evaluated. Comparisons were made between primary and revision endoprostheses. The relationship between resection level, range of motion, and time to failure were evaluated. Results: The average age was 69.9 yr with equal numbers of males and females. There were 13 primary and seven revision surgeries. The average follow-up was 40.9 mo. Eight patients experienced a failure requiring further surgical treatment: three soft tissue, two aseptic loosening, two infections and one tumor progression. The average range of motion was 65.86 degrees. The average resection length was 12.86 cm. Kaplan-Meier analysis showed no difference between failure or time to failure in primary versus revision procedures. There was a lower chance of failure with a resection level greater than 12 cm. There was no difference in range of motion and resection level. Conclusions: Distal humeral endoprostheses provide stable constructs in limb preserving surgeries. The complication profile is higher than standard total elbows. There was no difference in failures or time to failure between primary and revision surgeries. The major limitation of this study was the limited number of patients. It is one of the larger series evaluating distal humeral replacements.